Quantum walk of a Bose-Einstein condensate in the Brillouin zone - Alberti, Andrea; Wimberger, Sandro (Physical review, 2017)
We propose a realistic scheme to implement discrete-time quantum walks in the Brillouin zone (i.e., in quasimomentum space) with a spinor Bose-Einstein condensate. Relying on a static optical lattice to suppress tunneling in real space, the condensate is displaced in quasimomentum space in discrete steps conditioned upon the internal state of the atoms, while short pulses periodically couple the internal states. We show that tunable twisted boundary conditions can be implemented in a fully natural way by exploiting the periodicity of the Brillouin zone. The proposed setup does not suffer from off-resonant scattering of photons and could allow for a robust implementation of quantum walks with several tens of steps at least. In addition, on-site atom-atom interactions can be used to simulate interactions with infinitely long range in the Brillouin zone.
Gesehen am 17.04.2018